Food security perspectives in Sub-Saharan Africa - József Popp; Judit Oláh; Anna Kiss; Zoltán Lakner (Amfiteatru Economic Journal, 2019)
The state of global food security has been considerably improved in the last decades; however, these achievements are attributable to the 'green revolutions' in Latin-America and Asia. The food shortage has remained persistent in Sub-Saharan Africa, where the proliferation of undernourishment is nearly 30%. There is a large number of studies investigating different causes and aspects of the current crisis, or evaluating the future of the African agro-food sector based on one or a few particular aspects (e.g. climate change, population dynamics). Just a small number of attempts have been made to offer a holistic approach focusing on future development possibilities. The goals of the article are (1) to set up a conceptual system-dynamic model for agro-food development in Africa, (2) test this model on examples of two representative countries, namely Uganda and Nigeria, (3) based on expert surveys, define development scenarios for the agro-food sector in these two countries and (4) determine the key actions for the improvement of the present situation. The system dynamics simulations forecast a rather gloomy future for the agro-food sector: even the historically highest development rate of agricultural production of these two countries will not be enough to meet the rapidly increasing demand for food. Scenarios based on expert estimations predict long-range stagnation in Nigeria and just a moderate probability of improvement in Uganda. Radical improvement in the food security situation and prevention of imminent social catastrophe necessitate wide-ranging socio-economic reforms focusing on (1) decreasing fertility, (2) a general upgrading of health culture, (3) promotion of cooperatives and (4) enhanced attractiveness of the agro-food sector for a wide range of business investment opportunities.
Keywords: I12; L66; Q18; P46; 330; individual food security; food and nutritional insecurity; nutritional status; nutrition; nutrition education; population